Mon Nationalism and Civil War in Burma : the Golden Sheldrake. - South, Mr Ashley (Taylor and Francis, 2013)
A major contribution to the literature of Burmese history and politics, this book traces the rich and tragic history of the Mon people of Burma and Thailand, from the pre-colonial era to the present day. This vivid account of ethnic politics and civil war situates the story of Mon nationalism within the 'big picture' of developments in Burma, Thailand and the region. Primarily an empirical study, it also addresses issues of identity and anticipates Burmese politics in the new millennium. A particular feature of the book is its first-hand descriptions of insurgency and displacement, drawn from.